Decomposition of salix and populus leaves in the area of Lake Balaton and Kis-Balaton Wetland - Kucserka, Tamás; Simon, Brigitta; Anda, Angéla (GEORGIKON FOR AGRICULTURE, 2018)
Decomposition of plant litter in water influences metabolic processes, so its investigation has a major priority. In our study the aim was to determine Salix and Poplar leaf mass loss in a winter and in a summer period in presence and deprivation of macroinvertebrates in the area of Lake Balaton and Kis-Balaton Wetland. As a common method in the literature, leaf litter bag technique was used with small and big mesh sizes. Decomposition rates and chemical parameters of the water (pH, conductivity, NH4+, NO3-, SO42-, PO43-, Cl-) were determined. In summer decomposition was much faster, than in winter. In respect of the two study sites, leaves decomposed faster in Lake Balaton, compared to Kis-Balaton Wetland. In respect of the water chemical variables there was no significant difference between the water bodies and the sampling sites, either.
Keywords: leaf litter decomposition; Salix; Willow